Political Connections, Public Ownership, Firm Size and Corporate Social Responsibility Disclosure in Mining Companies Indonesia - Egia Praymesti; Rihfenti Ernayani; Butet Wulan Trifina (Cita konsultindo, 2026)
This study investigates the influence of political connections and public ownership on Corporate Social Responsibility (CSR) disclosure, with firm size serving as a moderating variable, in mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research is motivated by increasing public concern regarding environmental and social issues in Indonesia's mining sector, as well as inconsistent findings reported in previous studies concerning the determinants of CSR disclosure. A quantitative research design was employed using secondary data obtained from annual reports and financial statements. The sample consisted of 30 mining companies selected through purposive sampling, resulting in 120 firm-year observations. The hypotheses were tested using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS version 27. The empirical findings indicate that political connections significantly influence CSR disclosure, whereas public ownership does not have a significant effect. Furthermore, firm size strengthens the relationship between political connections and CSR disclosure but does not moderate the relationship between public ownership and CSR disclosure. These findings provide updated empirical evidence regarding the role of political connections and ownership structure in explaining CSR disclosure practices in Indonesia's mining industry and contribute to the development of legitimacy theory and corporate sustainability literature.